Tailoring Hydrogenation to Enhance Defect Suppression and Charge Transport in Hydrogenated Amorphous Silicon for Flexible Photodetectors - Ye‐ji Jeong; Kyeong‐jin Hyun; Hee‐Won Jang; Jong‐won Yun; Yong‐Hun Kim; Woon Ik Park; Soo‐Won Choi; Jung‐Dae Kwon (Advanced Science)
Abstract Visible‐light photodetectors (VPDs) garner significant attention due to their diverse applications in optical communication. However, conventional VPDs struggle to achieve both transparency and flexibility, limiting their use in emerging technologies. Hydrogenated amorphous silicon (a‐Si:H) offers a promising platform for flexible optoelectronics for compatibility with substrates, although temperature reduction causes degradation of electrical and optical properties due to insufficient hydrogen passivation. In this study, the effect of the hydrogen‐to‐silane (H2/SiH4; f ratio) gas is systematically investigated ratio on the microstructural, optical, and electrical properties of a‐Si:H films synthesized at an ultra‐low temperature of 90 °C using plasma‐enhanced chemical vapor deposition (PECVD). Raman and Fourier‐transform infrared (FT‐IR) spectroscopy reveal that an optimized H2/SiH4 ratio minimizes Si─H2 bonding, effectively reducing defect density and improving film stability. Spectroscopic ellipsometry confirms that this ratio optimizes the refractive index and optical bandgap, enhancing light absorption. Electrical measurements demonstrate that photodiodes with the optimized a‐Si:H layer exhibit superior photosensitivity and suppressed dark current (f2: 20.6 and f8: 2.70 × 10−10 A, respectively), attributed to improved carrier transport and reduced Shockley–Read–Hall (SRH) recombination. Furthermore, flexible photodetectors maintain high mechanical reliability under repeated bending cycles. These findings highlight the potential of ultra‐low‐temperature PECVD a‐Si:H films for high‐performance, flexible photodetectors.